Estratégias comunicacionais de interfaces gráficas de webjornais: estudo do caso Zero Hora.com - Grossmann, Fabiane Volkmer (2008)
With the purpose of noticing the occurrence of communication strategies in graphical interfaces (GI) of webjornals of fourth generation, this dissertation initiates the research considering GI as a mediator space which materializes the elements of humancomputer-human interaction grammar. The subject in focus is that such possibility for webjournals of fourth generation be thought in terms of communicational strategies applied in the creation of their GI as interagent captation strategies, not only in terms of metaphors, as it has been often seen in academic studies conducted so far. Throughout three chapters of literature review, three main reflections are carried out: a)one reflection which provides a different function to GI; b) another which identifies characteristics that classify the webjornal in a current fourth generation; and c) another reflection which proposes ways of materializing communication strategies, specifically strategies aimed at capturing the interagent. Such reflections are supported by theories of communication, midiatic communication, communicational strategies, interface design, and ergonomics. The discussion which that follows the theoretical construct is contextualized by the analysis of data obtained by the case study research methodology. The case study example, ZERO HORA.com, allowed some considerations to be outlined, which pointed NBR-9241 (following ISO-9241 recommendations, especially part 11, which deals with issues relating to the usability of systems) as a way to be taken towards the materialization of interagent captation strategies in the webjournals GI conception.